2003
DOI: 10.1016/s0010-0285(03)00035-5
|View full text |Cite
|
Sign up to set email alerts
|

Components of visual prior entry

Abstract: The prior entry hypothesis contends that attention accelerates sensory processing, shortening the time to perception. Typical observations supporting the hypothesis may be explained equally well by response biases, changes in decision criteria, or sensory facilitation. In a series of experiments conducted to discriminate among the potential mechanisms, observers judged the simultaneity or temporal order of two stimuli, to one of which attention was oriented by exogenous, endogenous, gaze-directed, or multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
218
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(231 citation statements)
references
References 87 publications
12
218
0
1
Order By: Relevance
“…Unfortunately, participants in psychophysical experiments seem rather prone to shifting their criteria based on incidental features of the question being asked (e.g Bedell, Chung, Ogmen & Patel, 2003;Clifford, Arnold & Pearson, 2003), and it has proven rather difficult to completely eliminate these biases . This is one reason that some investigators have suggested, albeit tentatively, that simultaneity judgements might make a better choice of task than temporal order judgements when the PSS is an important parameter for investigation (Schneider & Bavelier, 2003;van Eijk, Kohlrausch, Juola & van de Par, 2008;Zampini, Shore & Spence, 2005).…”
Section: Assumptions Underlying Analyses Of Tojsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, participants in psychophysical experiments seem rather prone to shifting their criteria based on incidental features of the question being asked (e.g Bedell, Chung, Ogmen & Patel, 2003;Clifford, Arnold & Pearson, 2003), and it has proven rather difficult to completely eliminate these biases . This is one reason that some investigators have suggested, albeit tentatively, that simultaneity judgements might make a better choice of task than temporal order judgements when the PSS is an important parameter for investigation (Schneider & Bavelier, 2003;van Eijk, Kohlrausch, Juola & van de Par, 2008;Zampini, Shore & Spence, 2005).…”
Section: Assumptions Underlying Analyses Of Tojsmentioning
confidence: 99%
“…To elucidate the often unstated assumptions underlying analyses of simultaneity data, we can take as a starting point the derivation provided by Schneider and Bavelier (2003). This derivation builds on work by Sternberg and Knoll (1973), Allan (1975) and Ulrich (1987).…”
Section: Assumptions Underlying Analyses Of Sjsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schneider & Bavalier [30] proposed a number of possibilities for how attention could affect TOJ: (i) through sensory interaction between cue and stimulus (exogenous attention), (ii) by reducing the transmission time of the attended stimulus (attending to a feature or spatial location) and (iii) by affecting the decision mechanism. Regarding (i), exogenous (visual) attention cues are by definition presented near the item to be attended; thus, sensory interactions are inevitable.…”
Section: Human Psychophysical Studiesmentioning
confidence: 99%
“…Should any behavioural facilitation of participants' performance in response to the visual target seen in such studies be accounted for in terms of an exogenous shift of spatial attention towards the location of the auditory cue, or to the multisensory integration of the cue and target stimulus into a single multisensory stimulus (cf. Schneider and Bavelier 2003)? At present, we simply do not know.…”
Section: Introductionmentioning
confidence: 99%